Pengaruh Karakteristik Tujuan Anggaran terhadap Kinerja Manajerial dengan Motivasi sebagai Variabel Intervening pada Pemerintah Daerah Kabupaten Merangin - Saukani, Saukani; Rasuli, M.; Darlis, Edfan (SOROT, 2015)
Abstract This study aims to determine the effect of the Budget on Performance Characteristics Purpose Managerial Motivation As an intervening variable. The present research of which data were collected using a questionnaires distributed to the SKPD structural officials of consisting of Echelon II, Echelon III, Echelon IV at the Regional Government of Merangin Regency. Of the 191 questionnaires distributed, 122 questionnaires were returned. There are 4 pieces of questionnaire were not completed, there were 118 questionnaires to be calculated in the present research. The analysis method was variant-based SEM using SmartPLS Software Version 2.0. From the results of the hypothesis testing of evidence that the motivation to act as mediating the relationship budgetary participation and managerial performance, budget goal clarity and managerial performance and budget goal difficulty and managerial performance. In the present study can not prove motivation as an intervening variable between the feedback budget and managerial performance and managerial performance evaluation budget.